Farmer groups as a tool for rural development programs: Perspectives from northwest highlands in Vietnam - Orduz, Daniela; Bravo, Aura; Pazos, Mateo; Cuong, Tran The; Nguyen, Thi Duong Nga; Hung, Pham-Van; Nguyen, Thi Thu Huyen; Trung, Ninh Xuan; Pam, Thi Le; Nguyen, Thinh; Triana Ángel, Natalia; Phuong, Nguyen Thi Minh; et al. (2025)
The formation of farmer groups (FGs) is central to rural development programmes promoted by NGOs and governments. These structures are widely recognised for their positive impacts, such as strengthening value chains, reducing transaction costs, creating economies of scale, and improving access to agricultural technologies. They also foster community trust, cooperation, and social cohesion. Despite these advantages, FGs face persistent challenges including dependence on external support, limited ability to mobilise operative capital, and difficulty sustaining their efforts over time. Northwest highlands Vietnam’s experience offers insights into the contextual conditions that shape the success or failure of collective farming models, especially considering their instrumental relevance in the sustainable transformation of agriculture. We argue for a comprehensive and intersectional approach that gives significant importance to local knowledge and cultural realities in the design of agricultural development interventions, especially when working with ethnic and marginalised minority populations. This study draws on an assessment of nine FGs in Son La Province, Mai Son District, as part of a CGIAR initiative to enhance beef and pork value chains through sustainable innovations for inclusive smallholder market participation. Through a qualitative, multi-stakeholder approach involving 124 interviews with group members, non-members, leaders, and local authorities, we identified constraints and opportunities at community, group, and structural levels. Key findings include the influence of land fragmentation, access to communal goods, and traditional livestock practices on technology adoption and then FGs performance. Cultural differences between Hmong and Thai communities significantly impact group dynamics: Hmong tend toward self-sufficiency and traditional grazing, while Thai groups are more market-oriented and adopt innovations more readily. Strong leadership emerges as a key factor in group success, helping to maintain activity and adapt to dynamic market circumstances. Finally, the ability of groups to define independent flexible, collective goals—beyond purely commercial aims—enhances their agency and resilience. Recognizing and supporting these diverse pathways is essential for designing inclusive and effective agricultural development interventions.